2016
DOI: 10.1080/15384101.2016.1203494
|View full text |Cite
|
Sign up to set email alerts
|

Loss of all 3 Extended Synaptotagmins does not affect normal mouse development, viability or fertility

Abstract: The extended synaptotagmins, E-Syt1, 2 and 3, are multiple C2 domain membrane proteins that are tethered to the endoplasmic reticulum and interact in a calcium dependent manner with plasma membrane phospholipids to form endoplasmic reticulum - plasma membrane junctions. These junctions have been implicated in the exchange of phospholipids between the 2 organelles. The E-Syts have further been implicated in receptor signaling and endocytosis and can interact directly with fibroblast growth factor and other cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…E‐Syt1 and E‐Syt2 are ubiquitously expressed in humans, whereas E‐Syt3 is mainly found in the nervous system (The Human Protein Atlas) (29, 30). Immunoblotting of mouse tissue confirmed the selective expression of E‐Syt3 in the brain, whereas E‐Syt1 and E‐Syt2 were detected in most tissues tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E‐Syt1 and E‐Syt2 are ubiquitously expressed in humans, whereas E‐Syt3 is mainly found in the nervous system (The Human Protein Atlas) (29, 30). Immunoblotting of mouse tissue confirmed the selective expression of E‐Syt3 in the brain, whereas E‐Syt1 and E‐Syt2 were detected in most tissues tested.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we find that E‐Syt1 acts as a negative feedback regulator of glucose‐stimulated insulin secretion by clearing the PM of DAG formed after insulin granule exocytosis. In previous work, it was shown that mice lacking all 3 E‐Syt isoforms are viable and exhibit no overt defects, although compensatory up‐regulation of other components of ER‐PM contacts was observed and may complicate the interpretation (29, 30). HeLa cells lacking all 3 E‐Syt isoforms exhibit reduced ER‐PM contact densities but show no major defects in overall lipid handling or Ca 2+ homeostasis (6).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, E-Syts have broad tissue distribution [36]. Surprisingly, their absence does not have a major disrupting effect on cellular life, as tricalbin triple knockout yeast cells and E-Syt triple knockout mammalian cells are viable [5, 6, 30].…”
Section: Open Questionsmentioning
confidence: 99%
“…Surprisingly, their absence does not have a major disrupting effect on cellular life, as tricalbin triple knockout yeast cells and E-Syt triple knockout mammalian cells are viable [5, 6, 30]. Additionally, mutant mice lacking all the three E-Syts develop normally, are viable and fertile [36, 37]. Thus, while it was reported that E-Syt2 is required for rapid endocytosis and signaling of growth factor receptors, including Fibroblast Growth Factor (FGF) receptor, such role is clearly dispensable in live animals [3840].…”
Section: Open Questionsmentioning
confidence: 99%
“…Reconstitutions of E-Syt1 and E-Syt2 in triple knockdown cells were sufficient to restore the abundance of ER-PM junctions to the control level, indicting the redundancy of E-Syts in ER -PM tethering. Triple E-Syt knockout animals are viable without obvious defects [136, 137]. These findings indicate that there are tethering mechanisms besides E-Syts maintaining ER-PM junctions.…”
Section: Recent Advances In Understanding the Regulation And Functmentioning
confidence: 99%